(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. In autosomal recessive distal renal tubular acidosis (DRTA), a substantial fraction of the patients have progressive bilateral sensorineural hearing loss. This coexistence is due to the mutations of a gene expressed both in the kidney and in the cochlea. The aim of this study was to assess the correlation between hearing loss and DRTA. Materials and Methods. In this study, 51 children diagnosed with renal tubular acidosis were evaluated. Diagnosis of DRTA was based on clinical manifestations and detection of normal anion gap metabolic acidosis, urine pH higher than 5.5, and positive urinary anion gap. Audiometry was performed in children with DRTA and sequencing of the ATP6V1B1 gene was done for those with sensorineural hearing loss. Results. Twenty-seven patients (52.9%) had DRTA, of whom 51.9% were younger than 1 year old, 55.6% were boys, and 44.4% were girls. Eleven patients (40.7%) had bilateral sensorineural hearing loss, consisting of 5 of 15 boys (33.3%) and 6 of 12 girls (50.0%). There was no correlation between hearing loss and gender. Three patients with hearing loss had mutation in the ATP6V1B1 gene (11.1% of patients with DRTA and 27.3% of patients with DRTA and hearing loss). Conclusions. This study indicated that a significant percentage of the children with DRTA had sensorineural hearing loss and mutation in ATP6V1B1 gene. It is recommended to investigate hearing impairment in all children with DRTA.